Increasing Autodesk Revit productivity for BIM projects : a practical guide to using Revit workflows to improve productivity and efficiency in BIM projects /: a practical guide to using Revit workflows to improve productivity and efficiency in BIM projects. (2021) - Roberti, Fabio; Ferreira, Decio
No abstract available